Stillbirths: ending preventable deaths by 2030. Issue 10019 (13th February 2016) - de Bernis, Luc; Kinney, Mary V; Stones, William; ten Hoope-Bender, Petra; Vivio, Donna; Leisher, Susannah Hopkins; Bhutta, Zulfiqar A; Gülmezoglu, Metin; Mathai, Matthews; Belizán, Jose M; Franco, Lynne; McDougall, Lori; et al.
Summary: Efforts to achieve the new worldwide goals for maternal and child survival will also prevent stillbirth and improve health and developmental outcomes. However, the number of annual stillbirths remains unchanged since 2011 and is unacceptably high: an estimated 2·6 million in 2015. Failure to consistently include global targets or indicators for stillbirth in post-2015 initiatives shows that stillbirths are hidden in the worldwide agenda. This Series paper summarises findings from previous papers in this Series, presents new analyses, and proposes specific criteria for successful integration of stillbirths into post-2015 initiatives for women's and children's health. Five priority areas to change the stillbirth trend include intentional leadership; increased voice, especially of women; implementation of integrated interventions with commensurate investment; indicators to measure effect of interventions and especially to monitor progress; and investigation into crucial knowledge gaps. The post-2015 agenda represents opportunities for all stakeholders to act together to end all preventable deaths, including stillbirths.